The The relationship between expressed emotion,family burden stigma and family support in patients with schizophrenia : Hubungan Ekspresi Emosi, Beban Keluarga, Dan Stigma Dengan Dukungan Keluarga Pada Pasien Dengan Skizofrenia - Komalasari, Lilis; Wardani, Ice Yulia; Winahayu, Neng Esti (Ruang Ide Publisher, 2024)
One of the problems that often occurs in families in caring for patients with schizophrenia is the emergence of family burden, emotional expression, and also stigma towards the family. This can affect families in caring for patients with schizophrenia, namely in providing family support. This study aims to identify and find the relationship between the level of emotional expression, family burden, family stigma, and family support in patients with schizophrenia in the psychiatric polyclinic of Dr. Soeharto Heerdjan Mental Hospital. This study used the Zarith Burden Interview, Family Questionnaire (FQ), Stigma items from the schedule for clinical assessment in neuropsychiatry (SCAN), and the Family Support Questionnaire. The research design was cross-sectional; the sampling technique used accidental sampling involving 82 families. Data analysis used univariate and bivariate analysis (chi-square test). The study's results showed that 48.8% of families had high emotional expression, 2.4% had heavy burdens, 51.2% had no burden, 92.7% had a stigma, and 54.9% were in the unsupportive category. The results of the correlation test showed that there was a significant relationship between emotional expression and family support (p-value = 0.028, α = 0.05), while family burden and stigma did not have a substantial relationship with family support (p-value family burden = 0.992 and p-value stigma = 0.685). The results of this study indicate that more effective family interventions are needed to increase family support and reduce stigma rates in families, namely through family education programs.